2021
DOI: 10.1108/sbm-02-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Does sport media raise her name? Examining intersectional representation in media narratives

Abstract: PurposeThe purpose of this research was to examine the role of intersectionality (multiple marginalized identities) in narratives used within online media coverage of women's sports. The authors adopted an intersectionality lens and drew from sports media literature to explore the representation of Black athletes in women's sport.Design/methodology/approachThe authors conducted a quantitative content analysis of online articles from ESPN, CBS Sports and Sports Illustrated from the 2020 WNBA Season. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In actuality, the argument falls quite flat when considering the additional dynamics related to sexism and lack of promotion for women's sports that undergirds the world of sport as a male-dominant space. And when mainstream media does cover the WNBA, researchers found that Black WNBA players receive less media attention than White WNBA players (Isard & Melton, 2021). Additionally, the study which looked at online articles from ESPN, CBS, and Sports Illustrated during the 2020 WNBA season also found that Black WNBA players who do not present in traditionally feminine ways receive the least amount of media attention, while White athletes have the freedom to express their gender in a variety of ways and still be featured in media stories (Isard & Melton, 2021).…”
Section: The Internal Wave Of Black Athlete Activismmentioning
confidence: 99%
“…In actuality, the argument falls quite flat when considering the additional dynamics related to sexism and lack of promotion for women's sports that undergirds the world of sport as a male-dominant space. And when mainstream media does cover the WNBA, researchers found that Black WNBA players receive less media attention than White WNBA players (Isard & Melton, 2021). Additionally, the study which looked at online articles from ESPN, CBS, and Sports Illustrated during the 2020 WNBA season also found that Black WNBA players who do not present in traditionally feminine ways receive the least amount of media attention, while White athletes have the freedom to express their gender in a variety of ways and still be featured in media stories (Isard & Melton, 2021).…”
Section: The Internal Wave Of Black Athlete Activismmentioning
confidence: 99%
“…In sports literature, intersectionality has been used to understand how multiple identities interact with one another. Examples include Simien et al (2019) identifying how Black woman athletes' lived experiences differ from those of other women, Isard and Melton (2022) quantitatively uncovering that traditionally feminine and white women receive the most attention in WNBA media coverage, and Ryan and Martin (2013) arguing for more intersectional work to be completed in the amateur sports world to understand how certain identities are privileged in certain spaces. Such studies are guideposts for instances in which intersectionality was effectively utilized in sport research.…”
Section: Intersectionalitymentioning
confidence: 99%
“…As one final example, we consider how Women's National Basketball Association (WNBA) players at present challenge the norms of women's sport. Women's sport has long asked women athletes to present in a hyper-feminine manner-a kind of compromise or accommodation between women athletes and the male preserve of sport (51). WNBA players have resisted this norm in recent years, embracing androgynous and masculine couture.…”
Section: Everyday Resistance Within Women's Sportmentioning
confidence: 99%
“…WNBA players have resisted this norm in recent years, embracing androgynous and masculine couture. Notably, the gap has narrowed between how a WNBA athlete expresses themselves off the court and in play ( 51 , 52 ). Today “There is more than one way to be a woman in basketball,” women’s sport journalist de la Cretaz concluded [( 51 ), para.…”
Section: Manifestations Of Everyday Resistance and Women’s Sportmentioning
confidence: 99%
See 1 more Smart Citation